Experimental study on bearing capacity of steel and steel fiber reinforced concrete composite beams without rebar cages. (April 2022) - Wu, Kai; Zhang, Yanjie; Lin, Shiqi; Leng, Fei; Xu, Chao
Abstract: In consideration of the interference between H-shaped steel and rebars and the difficulty of concrete pouring in SRC structure, steel fibers rather than the rebar cage in SRC beam are used to form the steel and steel fiber reinforced concrete (SSFRC) beams. Based on the two-point symmetrical loading experiments of 18 SSFRC specimens without rebar cages, the failure mode and load–deflection curve of each specimen were obtained. Thus, the effects of shear span ratio, H-shaped steel ratio and steel fiber volume ratio on the mechanical properties of beams were investigated. With the increase of the shear span ratio, the bearing capacity of the specimens presented a decreasing trend. Benefitting from the "bridging" effect of steel fibers, the failure mode of the specimen was less affected by the shear span ratio. When H-shaped steel ratio was greater, the bending and shear resistance of H-shaped steel could be fully utilized. Additionally, the composite action between materials was weakened when the thickness of concrete cover decreased. Increases in the steel fiber volume ratio could delay the elongation of cracks and reduce the sudden decrease of bearing capacity caused by the damage of the bonding interface between H-shaped steel and SFRC, therefore improving the bearing capacity. According to the superposition principle, the shearing capacity formula of SSFRC beam was proposed. By introducing the bond coefficient and considering the coupling effect of different parameters on the collaborative work of H-shaped steel and SFRC, the calculation formula of bending capacity with high accuracy was obtained. The coefficient could be used to objectively and quantitatively identify or predict the failure type of specimens, providing reference for engineering design.